2021
DOI: 10.1080/03323315.2021.1916562
|View full text |Cite
|
Sign up to set email alerts
|

Preservice teachers’ experiences of pandemic related school closures: anti-structure, liminality and communitas

Abstract: Initial Teacher Education (ITE) can be viewed as a formative space in professional teacher identity development. Practice plays a key role in shaping teacher identity, providing a window into the reality of school life, as well as nurturing professional autonomy. Due to the Covid-19 pandemic, school life shifted suddenly and unrecognisably in March 2020. This paper focuses on the experiences of preservice teachers on an ITE programme (post-primary) in one Irish University during the period of sudden school clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
0
15
1
Order By: Relevance
“…A recent study from Turkey also suggested that the pre-service teachers have the view point that 'online education is not as efficient as face-to-face education [9]. A study by White and McSharry [10] reported that the pandemic related closure of schools and online education acted as a sort of anti-structure, which in turn hindered the process of identity formation among the pre-service teachers. From the aforementioned studies it is clear that lack of familiarity with the online platform is the common theme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study from Turkey also suggested that the pre-service teachers have the view point that 'online education is not as efficient as face-to-face education [9]. A study by White and McSharry [10] reported that the pandemic related closure of schools and online education acted as a sort of anti-structure, which in turn hindered the process of identity formation among the pre-service teachers. From the aforementioned studies it is clear that lack of familiarity with the online platform is the common theme.…”
Section: Discussionmentioning
confidence: 99%
“…In support of the above-mentioned works, a study by White and McSharry (2021) also narrates how badly the sudden shift of teaching paradigms affected the pre-service teachers [10]. This study conducted during the COVID-19 lockdown at an Irish University during described that the sudden transition from face-to-face mode to online was problematic for the education itself.…”
Section: Introductionmentioning
confidence: 89%
“…In the present research, however, the tensions were merged into "using this vs that teaching technique" as the theories used as the basis in the blueprint were similar. Second, two new tensions, namely, "own teaching technique vs parents' demand" and "talking to peers vs keeping it to self" which were generated from the newer literature in the pandemic context (see Mecham et al, 2021;White & McSharry, 2021) were added to the current reflection form. Third, the wording for the guided reflection was also rewritten to suit the current situation better.…”
Section: Methodsmentioning
confidence: 99%
“…Instructors typically demonstrated a greater holistic orientation toward their students-what Christopher and her colleagues (2020, 824) refer to as "caring pedagogy"-rather than focusing largely on the mastery of course materials. We cannot confirm whether instructors believed they were both creative and innovative in DT/L (Turner, 2012;White & McSharry, 2021). However, by increasing opportunities for interaction and offering different support channels, instructors were able to maximize the chances of teaching relatively successfully in a digitally enabled format (Ray, 2021).…”
Section: Instructorsmentioning
confidence: 95%